Experimental study of changes in the intensity of infection of carp (Cyprinus carpio carpio) with blood parasites Trypanosoma carassii and Cryptobia borelli in the laboratory conditions - Guseinov, M. A. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
Experimental studies have shown that in the body of carp yearlings infested with trypanosomes and Cryptobia in the water with a low temperature (4–12°C), intensive aeration and abundant feeding intensity of infection of blood parasites was low. Intensity of infection of the same fish that were kept in water with temperature 20–24°C, poor aeration of water and shortage of food increased. The sharp increase of the intensity of infection with Cryptobia in one of the individuals led to the fish death.